Bacillus subtilis spore surface display enhances manganese peroxidase stability and stress resistance - Lu He; Mati Ullah; Muhammad Naeem; Zhong Ni; Yong Feng; Tawaf Ali Shah; Molalign Assefa; Khalid S. Almaary; Huayou Chen (Bioresources and Bioprocessing)
Abstract Manganese peroxidase (MnP) is in increasing demand due to its ability to degrade straw lignin and facilitate the conversion of agricultural waste into valuable feed resources. However, free MnP faces limitations in industrial applications owing to high operational costs, poor stability, and poor resistance to environmental stressors. In this study, MnP derived from Irpex lacteus was displayed on the surface of Bacillus subtilis spores using the cotB protein as an anchor molecule. Compared with refolded MnP expressed in E. coli, the spore-displayed MnP exhibited superior acid resistance, with an optimal pH of 3.5 (compared to pH 4.0 for the free enzyme). Additionally, the immobilized enzyme CotB-MnP retained 73.9% of its initial activity after incubation at 30℃ for 1 h incubation. Notably, immobilization eliminated the inhibitory effects of K⁺ and Zn²⁺ ions, which instead promoted the activity of the spore-displayed enzyme. The reusable spores maintained 69% of their initial activity after three consecutive cycles, highlighting their potential for industrial straw feed processing. Graphical Abstract